2008
DOI: 10.1021/ic7023567
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Laser Fluorescence Spectroscopy and Extended X-Ray Absorption Spectroscopy Investigations of the N3 Complexation of Eu(III), Cm(III), and Am(III) in an Ionic Liquid: Differences and Similarities

Abstract: The complexation of the lanthanide Eu(III) and the actinides Cm(III) and Am(III) by N3- was investigated by application of time-resolved laser fluorescence spectroscopy (TRLFS) and X-ray absorption spectroscopy (XAFS) in the ionic liquid solution of C4mimTf2N (1-butyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide). TRLFS measurements show that the interaction of azide with Eu(CF3SO3)3 and Eu(ClO4)3 results in both dynamic luminescence quenching by collisional encounters of N3- with Eu(III) and static l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…On a more general aspect, questions that are currently under study in our laboratory deal with comparison of Am/Eu kinetics in the TODGA/C 1 C n imTf 2 N system, because previous limited experiments already showed that in some cases, strong differences are to be found between the reactivity and the kinetics of Am, Eu and Cm in IL solvents. 42,43 This may also help to understand why some extraction systems in ILs display slow kinetics, while others are very fast.…”
Section: Resultsmentioning
confidence: 99%
“…On a more general aspect, questions that are currently under study in our laboratory deal with comparison of Am/Eu kinetics in the TODGA/C 1 C n imTf 2 N system, because previous limited experiments already showed that in some cases, strong differences are to be found between the reactivity and the kinetics of Am, Eu and Cm in IL solvents. 42,43 This may also help to understand why some extraction systems in ILs display slow kinetics, while others are very fast.…”
Section: Resultsmentioning
confidence: 99%
“…1 However, Naganawa et al reported an S.F. 20 Furthermore, an increase in metal ion extraction with increasing alkyl functionality in the ionic liquids in the case of Me-BTP did not support the conventional ion-exchange mechanism and an ion-pair mechanism may be proposed as given below: The lower extraction with ionic liquids having smaller alkyl groups may be attributed to a lower solubility of the bulky metal ligand ion-pair complexes containing 3 extractant molecules in the ionic liquid phase. 31 In a previous study, we reported an enhancement in the selectivity (S.F.…”
Section: Distribution Studies In [C N Mim]·[ntf 2 ]mentioning
confidence: 99%
“…[10][11][12] RTILs display higher stability under α and γ radiation. 20 From the observed differential behavior between An 3+ and Ln 3+ towards the N 3 − complexation in RTIL, they mentioned the possibility of using RTIL media for Ln 3+ /An 3+ separation using the selective extractants for An 3+ . 14 It is, therefore, important to explore the use of RTILs for process applications using radioactive elements with better recycling possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The structural information of other actinide ions dissolved in ionic liquids is relatively limited. By direct dissolving Am(ClO 4 ) 3 in [BMIm][Tf 2 N], Stumpf et al found that the first coordination shell contained about 11 oxygen atoms and the second coordination shell was composed of about 3–4 chlorine or sulfur atoms. When azide was added to the system, immediate detection showed that the number of oxygen atom in the first shell decreased to nine.…”
Section: Determination Of Actinide Speciation By Xafsmentioning
confidence: 99%